Dark Energy Survey Year 3 results: galaxy–halo connection from galaxy–galaxy lensing. Issue 3 (11th November 2021) - Zacharegkas, G; Chang, C; Prat, J; Pandey, S; Ferrero, I; Blazek, J; Jain, B; Crocce, M; DeRose, J; Palmese, A; Seitz, S; Sheldon, E; et al.
ABSTRACT: Galaxy–galaxy lensing is a powerful probe of the connection between galaxies and their host dark matter haloes, which is important both for galaxy evolution and cosmology. We extend the measurement and modelling of the galaxy–galaxy lensing signal in the recent Dark Energy Survey Year 3 cosmology analysis to the highly non-linear scales (∼100 kpc). This extension enables us to study the galaxy–halo connection via a Halo Occupation Distribution (HOD) framework for the two lens samples used in the cosmology analysis: a luminous red galaxy sample (redmagic ) and a magnitude-limited galaxy sample (maglim ). We find that redmagic (maglim ) galaxies typically live in dark matter haloes of mass log10 ( Mh /M⊙ ) ≈ 13.7 which is roughly constant over redshift (13.3−13.5 depending on redshift). We constrain these masses to ${\sim}15{{\ \rm per\ cent}}$, approximately 1.5 times improvement over the previous work. We also constrain the linear galaxy bias more than five times better than what is inferred by the cosmological scales only. We find the satellite fraction for redmagic (maglim ) to be ∼0.1−0.2 (0.1−0.3) with no clear trend in redshift. Our constraints on these halo properties are broadly consistent with other available estimates from previous work, large-scale constraints, and simulations. The framework built in this paper will be used for future HOD studies with other galaxy samples and extensions for cosmological analyses.